STUDI PENGADAAN PARK AND RIDE DI TERMINAL ALANG-ALANG LEBAR KOTA PALEMBANG - Yudhaprawira, Rio; Buchari, Erika; Arliansyah, Joni (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
With the rapid growth of population in line with rapid increasing of number of vehicles and vehicles ownership in Palembang, thus causes congestion in the streets, espescially in the center of town. Moreover, compounded by many vehicles parked on the street. One way to overcome these problems by diverting the private vehicles use to public transport modes, in addition, Park and Ride system must be applied in the terminals during will be heading to downtown Palembang The aim of this study is to determine the characteristics of the trip and measure the potential application of the park and ride system for people, this system is used to determine the magnitude of the supply needs of the vehicle that will carry out the transfer of the vehicle Park and Ride particularly in the Alang-alang lebar district area. The analysis conducted in this study is a descriptive analysis, analysis of origin-destination matrix and modal choices  matrix method is used with the base crosstabulation, and analysis of parking supply in the Alang-alang lebar terminal. In addition, before the analysis done, previously conducted Revealed Preference (RP) survey and traffic count to obtain more accurate data from this study. From the tesult of the research that has been conducted, the population with more frequent trip are males aged between 25-55 years with the status as a private employee and student, and the district with the most attracted trips are  Ilir Barat I and Sukarami, as well as the magnitude of potential Park and Ride vehicles in alang alang lebar area are 16.065 motorcycles and 2.768 cars.